1987
DOI: 10.2527/jas1987.642526x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Induced Corpora Lutea from Prepuberal Gilts and Spontaneous Corpora Lutea from Mature Gilts: In Vitro Progesterone Production1

Abstract: Prepuberal (P) gilts were induced to ovulate with pregnant mare serum gonadotropin followed 72 h later by human chorionic gonadotropin (hCG). Three P gilts and three mature (M) gilts each were ovariectomized on d 10, 14, 18, 22 and 26 (d 0 = day of hCG for P gilts and onset of estrus for M gilts). Gilts ovariectomized on d 14, 18, 22 and 26 were hysterectomized on d 6 to ensure maintenance of the corpora lutea (CL). Two to five grams of minced luteal tissue were dispersed using collagenase and hyaluronidase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Results from dispersed monolayers of luteal cells in culture indicate that prolactin and LH increase the rates of relaxin and progesterone secretion (Grinwich et al, 1983;Huang et al, 1991). Porcine luteal cells have prolactin-specific binding receptors (Rolland et al, 1976;Bramley & Menzies, 1987) and LH can stimulate progesterone secretion by these cells from the oestrous cycle and early pregnancy (Lemon & Loir, 1977;Hunter, 1981;Kineman & Rampacek, 1987), which is consistent with the present findings with ageing corpora lutea.…”
Section: Discussionsupporting
confidence: 80%
“…Results from dispersed monolayers of luteal cells in culture indicate that prolactin and LH increase the rates of relaxin and progesterone secretion (Grinwich et al, 1983;Huang et al, 1991). Porcine luteal cells have prolactin-specific binding receptors (Rolland et al, 1976;Bramley & Menzies, 1987) and LH can stimulate progesterone secretion by these cells from the oestrous cycle and early pregnancy (Lemon & Loir, 1977;Hunter, 1981;Kineman & Rampacek, 1987), which is consistent with the present findings with ageing corpora lutea.…”
Section: Discussionsupporting
confidence: 80%
“…Earlier studies of Kineman et al. (,b) compared steroidogenic enzyme system in CLs of prepubertal gilts induced to ovulate and spontaneous CL of mature gilts (after one or more oestrous cycles). Interestingly, 3 β HSD activity tended to increase in CLs collected from gonadotropin‐treated prepubertal gilts (Kineman et al.…”
Section: Discussionmentioning
confidence: 99%
“…P4 regulates the expression of several genes important for embryo-maternal interactions (for review see Spencer et al 2004;Ziecik et al 2011). Pharmacological manipulations to synchronize oestrus in domestic animals may cause decreased level of P4 in blood serum, which results from impaired luteal P4 metabolic pathway (Kineman et al 1987a) and reduced sensitivity to gonadotropic stimulation (Kineman et al 1987b;Skarzynski et al 2009). Low concentrations of circulating P4 altered the expression of endometrial genes that potentially contribute to histotroph composition and conceptus elongation in cattle (Forde et al 2011(Forde et al , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ratio of protein: DNA decreased slightly, though significantly, in both groups up to day 12 suggesting that the size of cells in CL had on average actually decreased (Baserga, 1985). Kineman et al (1987) observed no change in the proportion of large luteal cells per CL in dispersed cell preparations from hysterectomized pigs between day 10 and day 14. In view of the low mitotic rate of porcine lutein cells and the decrease in the ratio of luteal protein: DNA content it seems most likely that the increase in DNA content or cell numbers in the present study was due to increases in the number of smaller, nonsteroidogenic elements.…”
Section: Discussionmentioning
confidence: 69%
“…No evidence was presented to verify that the cell membrane antigenic components did not also change through the estrous cycle in either cell population however, and the identity of the proteins labelled by the antibodies was not recognized so that the expected specificty of each of the components could not be confirmed. In the pig, Kineman et al (1987) also presented data on large and small dispersed cell populations from CL collected from gilts at various times throughout the estrous cycle. These data also suggested that large luteal cells were more numerous during the later stages of the luteal phase.…”
Section: Morphology and Developmentmentioning
confidence: 99%